2017
DOI: 10.1021/jacs.7b08343
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Regioselective Monodefluoroborylation of Polyfluoroalkenes en Route to Diverse Fluoroalkenes

Abstract: Monodefluoroborylation of polyfluoroalkenes has been achieved in a regioselective manner under mild conditions via copper catalysis. The method has shown an extremely broad scope of substrates, including (difluorovinyl)arenes, tetrafluoroethylene (TFE), (trifluorovinyl)arenes, and trifluoromethylated monofluoroalkenes. The choice of boron source was important for the efficient transformation of (difluorovinyl)arenes; (Bpin) was suitable for substrates with an electron-deficient aryl group and (Bnep) for those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(125 citation statements)
references
References 43 publications
3
122
0
Order By: Relevance
“…Only two examples had previously been reported for the synthesis of this type of product, but small quantities of borylated fluoroalkenes were observed using polyfluoroalkenes as substrates. [28] In addition, treatment of 2 with N-chlorosuccinimide (NCS) or Nbromosuccinimide (NBS) furnished selectively either the monohalo-diborylated alkene (Cl and Br, 8 and 10) or the dihalo-monoborylated alkene (Cl and Br, 9 and 11) products in good yields, depending on the amount of NCS and NBS added and the reaction time. The structure of the 10 b was confirmed by single-crystal X-ray diffraction (see Figure S7).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Only two examples had previously been reported for the synthesis of this type of product, but small quantities of borylated fluoroalkenes were observed using polyfluoroalkenes as substrates. [28] In addition, treatment of 2 with N-chlorosuccinimide (NCS) or Nbromosuccinimide (NBS) furnished selectively either the monohalo-diborylated alkene (Cl and Br, 8 and 10) or the dihalo-monoborylated alkene (Cl and Br, 9 and 11) products in good yields, depending on the amount of NCS and NBS added and the reaction time. The structure of the 10 b was confirmed by single-crystal X-ray diffraction (see Figure S7).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[11][12][13][14][15][16][17] Only recently have methods emerged to convert unreactive CÀFb onds of HFOs into C À B, C À Si, or C À Ge bonds.F or example, Hosoya and coworkers presented an elegant defluoroborylation of (E)-1,3,3,3-tetrafluoropropene and 2,3,3,3-tetrafluoropropene with B 2 pin 2 (bis(pinacolato)diborane) using catalytic copper salts in the presence of abase. [18,19] In related studies,B raun and coworkers have documented the hydroboration, hydrosilylation, and hydrogermylation of aseries of fluoroalkenes (including HFOs) by Lewis acidic heterogeneous catalysts or homogeneous rhodium catalysts.T hese hydrofunctionalisation reactions often lead to complex mixtures of products because of competing addition and elimination pathways. [20][21][22] We,a nd others,h ave previously shown that the monomeric Al I reagent 1 reacts with C À Fb onds of fluoroalkanes and fluoroarenes; [23,24] herein, we describe the reaction of 1 with industrially relevant fluoroalkenes.This reactivity is an example of agrowing number of approaches in which alowvalent main-group metal mimics the redox behaviour of at ransition metal.…”
mentioning
confidence: 99%
“…Although fluoroalkenes are traditionally employed in organic and polymer chemistry as building blocks and monomers, they have received increasing attention in recent years as environmentally friendly substitutes for chlorofluorocarbons (CFCs) and hydrofluorocarbons (HFCs), [3] as ligands or substrates in transition-metal chemistry, [4] and as peptide isosteres. [5] For the analysis of the properties of fluorinated compounds, 19 F NMR spectroscopy can be employed. Thus, 19 F NMR spectroscopy was recently adopted for structural studies of enamines and ylides shifts, and the individual fluorocyclobutenes could not be identified.…”
Section: Introductionmentioning
confidence: 99%